The Effect of Self-Evacuation Drill on The Preparedness Level of Children with Disabilities in Facing Tornado Disaster - Serly Sani Mahoklory; Ferdinandus Suban Hoda (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Many of these casualties are high risk groups, one of which is children with disabilities.  This study aimed to investigate the preparedness level of children with disabilities in facing tornado before and after participating in the self-evacuation drills. This is a quasi-experimental study with one group pre- and post- test with control group design.  Results indicated that the preparedness level of children with disabilities in intervention group before intervention was 46.47 (±13.101), while in control group was 43.13 (±13.101). After intervention, the preparedness level in intervention group increased significantly compared to control group (p=0.000) and the mean of preparedness level in intervention group rose to 51.63 (±10.516) while control group did not record any increase with a mean of 41.20 (±12.288). These findings suggest that a learning method through a self-evacuation drill with audio-visual technique is more effective to improve the understanding of preparedness to face tornado among children with disabilities.